Biochemistry and Molecular Biology - Elliott, William H Elliott, Daphne C (OXFORD, 2005)
A concise introductory textbook in biochemistry and molecular biology for life sciences students taking a first course in the topic. Professor William Elliott from University of Adelaide, Dr Daphne Elliott formerly at Flinders University.